Mutation S110L of H1N1 Influenza Virus Hemagglutinin: A Potent Determinant of Attenuation in the Mouse Model - Nieto, Amelia; Vasilijevic, Jasmina; Santos, Nuno Brito; Zamarreño, Noelia; López, Pablo; Amorim, Maria Joao; Falcon, Ana (Frontiers in Immunology, 2019)
Characterization of a pandemic 2009 H1N1 influenza virus isolated from a fatal case patient (F-IAV), showed the presence of three different mutations; potential determinants of its high pathogenicity that were located in the polymerase subunits (PB2 A221T and PA D529N) and the hemagglutinin (HA S110L). Recombinant viruses containing individually or in combination the polymerase mutations in the backbone of A/California/04/09 (CAL) showed that PA D529N was clearly involved in the increased pathogenicity of the F-IAV virus. Here, we have evaluated the contribution of HA S110L to F-IAV pathogenicity, through introduction of this point mutation in CAL recombinant virus (HA mut). The HA S110L protein has similar pH stability, comparable mobility, and entry properties both in human and mouse cultured cells that wild type HA. The change HA S110L leads to a non-significant trend to reduce the replication capacity of influenza virus in tissue culture, and HA mut is better neutralized than CAL virus by monoclonal and polyclonal antibodies against HA from CAL strain. In addition, recombinant viruses containing HA S110L alone or in combination with polymerase mutations considerably increased the LD50 in infected mice. Characterization of the lungs of HA mut infected animals showed reduced lung damage and inflammation compared with CAL infected mice. Accordingly, lower virus replication, decreased presence in bronchioli and parenchyma and lower leukocytes and epithelial infected cells were found in the lungs of HA mut-infected animals. Our results indicate that, mutation HA S110L constitutes a determinant of attenuation and suggest that its interaction with components of the respiratory tract mucus and lectins, that play an important role on influenza virus outcome, may constitute a physical barrier impeding the infection of the target cells, thus compromising the infection outcome.